Asynchronous education improves emergency medical services clinician confidence and knowledge in caring for patients near the end‐of‐life - David H. Wang; Charles Dunn; Justin K. Brooten; Brian Gacioch; Michael Taigman; Zili He; James Dziura; Amelia M. Breyre (Journal of the American College of Emergency Physicians Open)
Abstract Objective To evaluate the impact of a nationally available continuing education online curriculum on Emergency Medical Services (EMS) clinician confidence and knowledge in caring for end‐of‐life (EOL) patients. Methods This is a prospective observational study of EMS clinicians (emergency medical technicians [EMTs], advanced EMTs [AEMTs], and paramedics). EMS clinicians and physicians with both EMS and palliative care expertise developed two 20‐min modules regarding: (1) communication skills (including death notification) and (2) hospice knowledge. EMS clinicians’ subject confidence (modified Likert‐scale) and knowledge were assessed electronically immediately before and after each module. Data analysis compared before and after module improvements in knowledge and confidence. Linear regressions analyzed baseline EOL skill confidence scores based on EMS agency, level of certification, and years of experience. Results We analyzed completed datasets for 1825 EMS clinicians (979 EMTs, 112 AEMTs, and 734 paramedics) representing a heterogeneous cohort across different EMS agencies (617 private, 545 fire‐based, 298 hospital‐based, 61 third service, and 304 other) and all 50 states and the District of Columbia. After the communication module, the number of EMS clinicians who reported confidence in delivering bad news increased from 62% (1131/1825) to 80% (1468/1825) (p < 0.001). After the hospice module, the number of EMS clinicians who reported confidence in knowing what services hospice provides increased from 51% (925/1825) to 75% (1375/1825) (p < 0.001) and confidence in knowing what active dying patients look like from 57% (1033/1825) to 78% (1429/1835) (p < 0.001) in knowing what active dying patients look like. Linear regression demonstrated that before modules, EMS clinicians with more monthly EOL calls, those with more years of experience, and paramedics were more confident in their EOL skills than their peers. After module completion, those with the fewest years of experience (0–3 years) and EMTs gained significantly more confidence in communication skills than their peers. Conclusion Asynchronous, online continuing education improves EMS clinician knowledge and confidence in caring for patients near the EOL. The greatest benefit in improved confidence was for EMTs and those with the fewest years of EMS experience.